Beyond Formal Metrology: The Socio-Legal Construction of Traditional Measurement in Shellfish Trading within a Muslim Coastal Community in Tempurukan - Yolanda, Vhadia; Ardiansyah; Widiyawati, Ari (Elkuator Research and Publication, 2025)
This article examines the socio-legal construction of shellfish trading practices that utilize traditional measuring tools within the Muslim coastal community of Tempurukan Village, Ketapang, West Kalimantan. The study is motivated by the limited scholarly attention given to how traditional measurement systems in coastal economies interact with Islamic law, particularly in commercial practices that do not employ standardized metrological instruments. Adopting a socio-legal approach, the field research applies Peter L. Berger and Thomas Luckmann’s social construction theory to analyze the dynamics of these practices. Data were collected through structured interviews with nine informants, participant observation, and documentation of transactional processes. The findings reveal that the community uses cupak (coconut-shell measures) and ringkat (plastic containers) as traditional measuring devices, socially regarded as equivalent to one kilogram. This non-standard measurement system is grounded in inherited tradition, social trust, and practical efficiency, and is considered valid within Islamic law because it fulfills the principle of tarāḍin (mutual consent) and falls under the category of ʿurf ṣaḥīḥ (sound custom). Through the processes of externalization, objectivation, and internalization, the cupak has evolved into a socio-legal instrument that negotiates customary norms, economic rationality, and Islamic ethical values. The article argues that this socially constructed system produces a form of justice rooted in local wisdom that transcends the precision-oriented logic of modern metrology, reflecting a distinctive pattern of local Islamic legal reasoning within the coastal Muslim community. [Artikel ini menganalisis konstruksi sosio-legal praktik jual beli kerang dengan menggunakan alat ukur tradisional pada masyarakat muslim pesisir di Desa Tempurukan, Kabupaten Ketapang, Kalimantan Barat. Penelitian ini berangkat dari minimnya perhatian akademik terhadap bagaimana sistem ukur tradisional dalam ekonomi pesisir berinteraksi dengan hukum Islam, khususnya dalam praktik jual beli yang tidak menggunakan alat metrologi standar. Penelitian lapangan ini menggunakan pendekatan sosio-legal dan dianalisis dengan teori konstruksi sosial Peter L. Berger dan Thomas Luckmann. Data diperoleh melalui wawancara terstruktur terhadap sembilan informan, observasi partisipan, dan dokumentasi proses transaksi. Hasil penelitian ini menemukan bahwa masyarakat muslim pesisir menggunakan cupak (batok kelapa) dan ringkat (wadah plastik) sebagai alat ukur yang secara sosial dianggap setara dengan satu kilogram. Sistem ukur non-standar ini dilandasi tradisi turun-temurun, kepercayaan sosial, dan efisiensi praktis, serta dipandang sah secara fikih Islam karena memenuhi prinsip tarāḍin (kerelaan bersama) dan termasuk dalam kategori ʿurf ṣaḥīḥ (kebiasan yang baik). Melalui proses eksternalisasi, objektivasi, dan internalisasi, cupak berkembang menjadi instrumen sosio-legal yang menegosiasikan nilai adat, rasionalitas ekonomi, dan etika Islam. Artikel ini berargumen bahwa konstruksi sosial tersebut menghasilkan bentuk keadilan berbasis kearifan lokal yang melampaui logika presisi metrologi modern serta merefleksikan pola penalaran fikih lokal yang khas dalam masyarakat muslim pesisir.]